2020
DOI: 10.1093/cid/ciaa459
|View full text |Cite
|
Sign up to set email alerts
|

Testing for SARS-CoV-2: Can We Stop at 2?

Abstract: The COVID-19 epidemic requires accurate identification and isolation of confirmed cases for effective control. This report describes the effectiveness of our testing strategy and highlights the importance of repeat testing in suspected cases in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 6 publications
1
49
0
1
Order By: Relevance
“…19 The requirement for 2 tests 24 hours apart was supported by local studies demonstrating increased testing yield due to the possibility of intermittent viral shedding or variations in sampling technique. 20 For patients admitted into the RSW with a primary nonrespiratory condition who concomitantly had URTI, SARS-CoV-2 testing was performed if the patient was to be transferred from the designated wards, with the caveat that testing should only be done at day 5 of symptoms. This procedure was supported by local studies that obtained good testing yield when sampling patients presenting with a median of 5 days of symptoms.…”
Section: Respiratory Surveillance Wards (Rsws): Admissions Criteria mentioning
confidence: 99%
See 1 more Smart Citation
“…19 The requirement for 2 tests 24 hours apart was supported by local studies demonstrating increased testing yield due to the possibility of intermittent viral shedding or variations in sampling technique. 20 For patients admitted into the RSW with a primary nonrespiratory condition who concomitantly had URTI, SARS-CoV-2 testing was performed if the patient was to be transferred from the designated wards, with the caveat that testing should only be done at day 5 of symptoms. This procedure was supported by local studies that obtained good testing yield when sampling patients presenting with a median of 5 days of symptoms.…”
Section: Respiratory Surveillance Wards (Rsws): Admissions Criteria mentioning
confidence: 99%
“…This procedure was supported by local studies that obtained good testing yield when sampling patients presenting with a median of 5 days of symptoms. 20 Additionally, because patients with URTI symptoms were generally more well, this approach conserved testing resources in the initial phase of the outbreak. From March 1 onward, all patients with URTI alone had 1 swab done on admission, followed by the second swab on day 5 of symptom onset.…”
Section: Respiratory Surveillance Wards (Rsws): Admissions Criteria mentioning
confidence: 99%
“…All admitted suspect cases received an initial chest x‐ray and were tested for SARS‐CoV‐2 by means of RT‐PCR from respiratory specimens over two consecutive days . Clinicians were given the liberty to perform additional tests based on clinical or epidemiological grounds.…”
Section: Singapore's Covid‐19 Responsementioning
confidence: 99%
“…Initial NP RT-PCR testing is more sensitive than OP testing in both severe (73.3% versus 60.0%) and mild (72.1% versus 61.3%) COVID-19 cases [29]. A separate study demonstrated improvement in NT-PCR sensitivity (from 88.6%-95.7%) when repeated after 24 hours in patients who initially tested negative [30]. Thus, NP RT-PCR is the current recommended investigation [31].…”
Section: Preoperative Testingmentioning
confidence: 99%